Influence of trichomes on attractiveness and ovipositional preference of Bemisia tabaci (Genn.) B biotype (Hemiptera: Aleyrodidae) on tomato genotypes - Oriani,Maria A de G (2010)
Brazil is one of the world's largest tomato producer, but considerable part of the production is lost due to the attack of Bemisia tabaci (Genn.) B biotype. Resistant germoplasm plants can be an important method for B. tabaci control in integrated pest management approaches. The attractiveness and ovipositional preference of B. tabaci for 17 tomato genotypes were evaluated in a free-choice test. Trials were set up in a randomized block design with ten replicates. Each replicate (one tomato plant per pot) was placed in a cage (80 x 50 x 50 cm) and infested with 1,000 adults during four days. Linear correlation tests were applied between the number of insects and eggs and number of trichomes in each tomato genotype. LA716, LA444-1 and PI134418 genotypes were the least attractive, while the 'Santa Clara' was the most attractive; PI134417 trapped the largest number of adults. LA716 genotype (4.1 eggs/leaflet and 2.1 cm²/eggs per leaflet) was the least preferred for whitefly oviposition; NAV1062, 'Fanny', LA1335, 'Santa Clara' and IAC294 were the most preferred genotypes. The glandular trichomes density was negatively correlated with whitefly's attractiveness and oviposition per leaflet and per leaf, and positively with the number of trapped insects. The non-glandular trichomes density was negatively correlated with the number of trapped insects and positively with whitefly's oviposition per cm²/leaflet andper cm²/leaf. LA716 had high antixenosis level (ovipositional nonpreference) toward B. tabaci B biotype related with type IV glandular trichome.